2019
DOI: 10.20900/cbgg20200003
|View full text |Cite
|
Sign up to set email alerts
|

Cultivated Grapevine Displays a Great Diversity for Reproductive Performance Variables

Abstract: Background: There are thousands of grapevine varieties that display a wide range of variation for traits like grape use (wine, table grape or both), color or ripening time, but little is known about their reproductive performance, especially flowering and fruitset (conversion from flower to fruit). Works focused at the study of these traits in grapevine evaluated one or few varieties and used different methodologies making comparisons difficult. This study aimed to characterize the reproductive performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…The highest value of 68% corresponded to Godello (Cenlle 2017), while the lowest coulure value of 17% was registered for Mencía (Souto 2017). Despite these results, previous studies pointed out high fruitset rates for Godello variety, higher than 90% [23], which means that the highest coulure value found in the present study, of 68% for the Godello variety in Cenlle 2017, could be due to environmental conditions, such as meteorological or phytopathological conditions, which could affect the fertilization process and fruitset. In general, the mean coulure value for each variety was also higher for Godello, with 40.5%, than for Mencía, with 31%.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The highest value of 68% corresponded to Godello (Cenlle 2017), while the lowest coulure value of 17% was registered for Mencía (Souto 2017). Despite these results, previous studies pointed out high fruitset rates for Godello variety, higher than 90% [23], which means that the highest coulure value found in the present study, of 68% for the Godello variety in Cenlle 2017, could be due to environmental conditions, such as meteorological or phytopathological conditions, which could affect the fertilization process and fruitset. In general, the mean coulure value for each variety was also higher for Godello, with 40.5%, than for Mencía, with 31%.…”
Section: Discussioncontrasting
confidence: 94%
“…These reproduction functioning variations among the different grapevine varieties are reflected, as well, on reproductive performance variables, such as the number of flowers and berries per inflorescence/bunch or the production of pollen grains by the plant. A recent study characterized the reproductive performance of 120 grapevine varieties, the largest comparative study done in this field, in which a great diversity was found for most variables, including fruitset and the number of flowers [23]. They obtained a clustering of similar varieties, in which groups were related with the variety use (table, wine, or both) and its geographical origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high yield for these genotypes might be a result of genetic expression, as these two genotypes were also characterized as highly productive in field phenotyping experiments ( Wilhelm de Almeida et al., 2023a ). Genetic variability within grapevine yield formation was previously observed in regards to bunch number per shoot ( Grzeskowiak et al., 2013 ), number of inflorescence per flower and in fruit set rate ( Ibáñez et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%